Critical Discourse Analysis on Islam Nusantara in Indonesia's Foreign Policy - Rizki Dian Nursita (Hasanuddin Journal of International Affairs, 2023)
The concept of Islam Nusantara is a concept and perspective of Islam that Nahdlatul Ulama promoted at the NU Congress in 2015. It is used to mention the indigenization of Islamic practice in Indonesia, often contrasted with Arabization. The discourse of Islam Nusantara which is developing well among the government, Islamic organizations, and the community is aging several pros and cons for Indonesia's domestic politics. Furthermore, Islam Nusantara is also often used as the trademark of Indonesia's foreign policy with countries in the Middle East. This study tries to explain how Islam Nusantara Islam as a discourse has been applied in Indonesia's foreign policy towards countries in the Middle East. The study primarily relies on a critical discourse analysis method.